2020
DOI: 10.1162/jocn_a_01596
|View full text |Cite
|
Sign up to set email alerts
|

Holding On to the Past: Older Adults Show Lingering Neural Activation of No-Longer-Relevant Items in Working Memory

Abstract: Goal-relevant information can be maintained in working memory over a brief delay interval to guide an upcoming decision. There is also evidence suggesting the existence of a complementary process: namely, the ability to suppress information that is no longer relevant to ongoing task goals. Moreover, this ability to suppress or inhibit irrelevant information appears to decline with age. In this study, we compared younger and older adults undergoing fMRI on a working memory task designed to address whether the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 75 publications
3
17
0
Order By: Relevance
“…The concept of age deficits in inhibitory control has received much attention in the past, especially given the evidence that older adults' working memory performance is disproportionately impacted by the presence of distractors (for review see Lustig et al, 2007). This wealth of behavioral studies motivated recent fMRI research which employed working memory paradigms to demonstrate that older adults show less down-regulation of cortical activity in regions responsive to task-irrelevant stimuli (Chadick & Gazzaley, 2011;Chadick et al, 2014;Gazzaley et al, 2005Gazzaley et al, , 2008Weeks et al, 2020).…”
Section: Age Differences In the Control Of Cortical Reinstatementmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of age deficits in inhibitory control has received much attention in the past, especially given the evidence that older adults' working memory performance is disproportionately impacted by the presence of distractors (for review see Lustig et al, 2007). This wealth of behavioral studies motivated recent fMRI research which employed working memory paradigms to demonstrate that older adults show less down-regulation of cortical activity in regions responsive to task-irrelevant stimuli (Chadick & Gazzaley, 2011;Chadick et al, 2014;Gazzaley et al, 2005Gazzaley et al, , 2008Weeks et al, 2020).…”
Section: Age Differences In the Control Of Cortical Reinstatementmentioning
confidence: 99%
“…However, despite the wealth of behavioral studies examining age deficits in WM, neuroimaging evidence for the inhibitory deficit hypothesis is relatively sparse. Nonetheless, extant findings suggest that older adults demonstrate reduced ability to strategically downregulate cortical activity in regions selectively responsive to specific classes of perceptual information (Chadick & Gazzaley, 2011;Chadick et al, 2014;Gazzaley et al, 2005Gazzaley et al, , 2008Weeks et al, 2020). For example, Chadick et al (2014) reported that when participants were presented with overlapping images of a face and a scene in a delayed match to sample task, younger adults demonstrated attenuated activity in the parahippocampal cortex (relative to a 'no-task' baseline) when the scenes were task-irrelevant, and enhanced activity in the same region when they were task-relevant.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the interference may be occurring entirely within working memory, as information from previous trials has not been sufficiently removed or inhibited from active maintenance (see also Oberauer et al, 2017 ). Previous work has demonstrated that older adults are less efficient than younger adults at inhibiting no-longer-relevant information (Hasher et al, 2007 ; Lustig et al, 2001 ; Oberauer, 2001 , 2005 ; also, see Weeks et al, 2020 , for recent fMRI evidence of this), but whether or not previously learned information is more likely to interfere with older adults’ performance on a working memory task is, arguably, a separate issue. Oberauer et al ( 2017 ) also make this point about the wider literature where many instances of supposed interference from long-term memory in working memory tasks could instead be attributable to insufficient removal of information from working memory between trials.…”
mentioning
confidence: 99%
“…Older adults' tendency to report the salient, but no longer relevant, cued item may reflect their lessened ability to inhibit previously attended information when it becomes task irrelevant, a process that is sometimes referred to as deletion or working memory updating [39,40,62,70,71]. In line with this proposal, older adults have recently been shown to display greater neural activation for no-longer-relevant items during working memory maintenance, an effect that predicts worse recall performance for relevant items [72]. Thus, older adults may have difficulty inhibiting irrelevant items especially when they were once assigned higher priority.…”
Section: Discussionmentioning
confidence: 94%